Managing the non-profit organization : practices and principles - Drucker, Peter F. (Peter Ferdinand), 1909-2005. (New York, N.Y. : Collins Business, 2005)
Including interviews with Frances Hesselbein, Max De Pree, Philip Kotler, Dudley Hafner, Albert Shanker, Leo Bartel, David Hubbard, Robert Buford, and Roxanne Spitzer-Lehmann.
Includes index.
Keywords: Nonprofit organizations -- Management; Associations, institutions, etc. -- Management